Implementasi Media Audio Visual sebagai Upaya Meningkatkan Hasil Belajar IPA pada Siswa Kelas V SDN 2 Jayagiri - Rani Sri Rahayu; Akhmad Nugraha (Kilau Publishing, 2025)
This study was motivated by the low motivation and learning outcomes of fifth-grade students in Natural Science at SDN 2 Jayagiri, Panumbangan District, Ciamis Regency. The study aimed to determine the improvement in students’ learning outcomes through the use of audio-visual media in Natural Science learning. This research employed Classroom Action Research conducted in two cycles. The subjects of the study were 23 fifth-grade students of SDN 2 Jayagiri in the 2024/2025 academic year. Data were collected through observation, learning achievement tests, and documentation, and then analyzed using qualitative and quantitative descriptive techniques. The criterion for success was established when more than 75% of students achieved the Minimum Mastery Criterion (KKM). The results showed that the percentage of students’ learning mastery increased from 47.8% in the pre-cycle to 56.5% in Cycle I, and reached 95.6% in Cycle II. Thus, the use of audio-visual media was proven to improve the Natural Science learning outcomes of fifth-grade students at SDN 2 Jayagiri. The implication of this study confirms that audio-visual media are appropriate to be used as an alternative instructional medium to enhance student engagement and learning outcomes in elementary schools.